2014
DOI: 10.1128/cvi.00370-14
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Available Complement Component-Depleted Sera Are Unexpectedly Codepleted of Ficolin-2

Abstract: The ficolins are a family of innate pattern recognition molecules that are known to bind acetylated compounds and activate complement through the association of mannose binding lectin (MBL)/ficolin-associated serine proteases (MASPs). Their importance has more recently become appreciated, as they have been shown to play a role in a variety of disease processes from infection to autoimmunity. While studying ficolin-2-mediated complement deposition on Streptococcus pneumoniae, we found that sera depleted of C1q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In line with our observations, C1q-mediated enhancement of efferocytosis was previously shown to be independent on the quantity of C1q bound to dying cells [41]. However, as C1q depletion from serum was shown to also affect the levels of other factors involved in AC clearance such as properdin, Factor D [15] and ficolin-2 [31], we cannot exclude that lack of one or more of these other factors may have partly affected phagocytosis in depleted serum.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with our observations, C1q-mediated enhancement of efferocytosis was previously shown to be independent on the quantity of C1q bound to dying cells [41]. However, as C1q depletion from serum was shown to also affect the levels of other factors involved in AC clearance such as properdin, Factor D [15] and ficolin-2 [31], we cannot exclude that lack of one or more of these other factors may have partly affected phagocytosis in depleted serum.…”
Section: Discussionsupporting
confidence: 88%
“…Physiologic clearance of apoptotic cells takes place very rapidly [28,29], and dead cell accumulation occurs only under certain pathogenic conditions [30]. While efforts have been made in vitro to dissect the relative importance of C1q from downstream complement components, artificial depletion of individual complement components from normal sera has been shown to cause reduction of other serum factors [15,31], and serum obtained from patients with complement deficiencies usually has elevated cytokines and autoantibodies that may confound interpretation of the results [32,33]. We reasoned that specific inhibition of enzymatic C1s activity would be expected to leave C1q binding to AC unaffected, while blocking classical pathway-mediated activation of C3.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have reported the specific inhibition of ficolin-2 by the coating in plastic serum collection tubes (Brady et al, 2014c; Hein et al, 2013), and others have observed the depletion of ficolin-2 by heparin-treated cardio bypass circuits (Hein et al, 2015). Ficolin-2 was observed to bind to derivatized Sepharose (Kilpatrick & Chalmers, 2012), and commercial complement component-depleted sera are deplete of ficolin-2 as well (Brady et al, 2014b). Ficolin-2 studies therefore require careful consideration of various analytical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples (3 µl per lane) were assayed for ficolin-2 by SDS-12%PAGE as previously described (Brady et al, 2014b). …”
Section: Methodsmentioning
confidence: 99%
“…BC069825 ) in pcDNA3.1(−) was described previously (Brady et al, 2014a; Brady et al, 2014b). All cell culture was performed in a humidified 37°C incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%